Genèse de l’économuséologie - Vaillancourt Laporte, Marie (Material Culture Review, 2015)
Since its beginnings, the economuseum model calls into question the communal values of the major museumsscene in Québec, by creating an alternative museum network. More than twenty years after its creation, the Société du réseau économusée (Society of the Economuseum Network) and its innovative concepts such as the preservation of intangible cultural heritage as well as the interest in a self-financing model, have come a long way. However, economuseums have not yet garnered official recognition of their museum status. In light of these questions, it is necessary to study the genesis of economuseology, intimately intertwined in the professional development of Mgr Félix-Antoine Savard and of Cyril Simard.